First report on the occurrence of psoroptic mange in llamas (Lama glama) of the Andean region - Sosa, Fabiana Evangelina (2024)
An outbreak of Psoroptes sp.-caused mange was detected in a llama herd of Larcas, Jujuy province, Argentina. Infested llamas showed alopecia, erythema, hyperpigmentation, hyperkeratosis, and inflammation of the ear pinnae, as well as crusts and serous, serosanguineous, or purulent drainage with unpleasant smell in the external ear canal. Microscopic evaluation of skin scrapings revealed 0.5- to 0.7-mm-long acari identified as Psoroptes sp. based on their morphology. Histology showed a typical allergic reaction with perivascular to periadnexal mixed inflammatory infiltrate. Phylogenetic tree analysis showed that the cytochrome c oxidase subunit I gene sequences analyzed from the sampled acari clustered into a single P. ovis clade including sequences isolated from rabbits and bighorn sheep, with P. natalensis as a sister taxon that infested bighorn sheep from the USA. Phylogenetic analysis of cytochrome b sequences showed three well-supported clades, one of which contained the sequences of the Larcas llamas and US bighorn sheep isolates. This is the first report on P. ovis infestation of llamas raised in their original location. Investigations on mange etiological agents acting on South American camelids and their distribution are necessary to implement control strategies to mitigate the negative impacts of these parasitic infections.